Delivery of women's healthcare across the UK during the Covid-19 pandemic - Michael Rimmer (Ubiquity Proceedings, 2022)
The nature of global health crises means their impact is both wide-reaching and affects all aspects of society. The full extent of how this impacts different groups, notably the marginalised and minorities, is often not fully understood until years later, if at all. The Covid-19 pandemic has been no different. Yet, despite the pandemic being far from over, the way we collect data on routine health outcomes means we can gain early insights as to how the pandemic has impacted different groups within society. This is particularly relevant to women’s health care which is often acute. The impact of Covid-19 on pregnancy outcomes in particular have come under significant scrutiny with an increase in poor health care outcomes identified through routine data collection across several countries.